Prevalence of Mood and Anxiety Disorders Among Adults Seeking Care in Primary Healthcare Centers in Cordoba, Argentina. - Burrone, María Soledad; Alvarado, Rubén; Colantonio, Lisandro D.; Enders, Julio E.; Abeldaño Zuñiga, Roberto Ariel; Valencia, Eliecer; Susser, Ezra; Fernández, Ruth A. (Frontiers in Psychiatry, 2020)
Objective: To estimate the prevalence of mental disorders (MD) among adults seeking care for general health problems in public (i.e., government-funded) primary healthcare centers in Cordoba city, Argentina. Methods: Cross-sectional analysis of adults 18-69 years of age seeking care for general health problems in public primary healthcare centers in Cordoba city, Argentina in 2010-2011. Participants were randomly selected using a probabilistic, stratified, multi-stage sampling design. MD, including anxiety and mood disorders, were assessed in the participants’ lifetime, and in the last 12 months and 30 days using the World Mental Health Composite International Diagnostic (CIDI). MDs were defined following the International Classification of Diseases, tenth revision. Results: Overall, 1,067 participants were included in the current analysis (mean age 35.6 [SD 13.2] years, 83.7% female). The lifetime, 12-month and 30-day prevalence of MD was 40.4% (95% confidence interval [95%CI] 37.4%-43.4%), 20.1% (17.8%-22.7%) and 7.8% (6.2%-9.6%), respectively. The occurrence of anxiety disorders was higher compared to mood disorders when assessed in the participants’ lifetime (29.7% [95%CI 27.0%-32.5%] versus 19.3% [17.0%-21.8%]), and in the last 12 months (14.9% [12.8%-17.2%] versus 8.7% [7.1%-10.6%]) and 30 days (5.8% [4.5%-7.4%] versus 2.3% [1.5%-3.4%]). Age and marital status-adjusted odds ratios for MD in the participants’ lifetime and in the last 12 months and 30 days comparing women versus men were 1.19 (95%CI 0.85-1.67), 1.70 (1.07-2.69) and 2.26 (1.02-5.00), respectively. Conclusion: Prevalence of MD is high among adults seeking care in primary healthcare centers in Cordoba, particularly among women. Integration of primary and mental health services is warranted.